Trimmed off adipocytes: a source of newly secreted adipokines - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Abdul Rahman, Suzanah; Syed Osman Idid, Syed Zahir Idid; Phang, Ing Chia; Md Isa, Muhammad Lokman; Md Aris, Mohd Aznan; Bakhtiar, M. Taher (Mattioli 1885 S.p.A., 2019)
Given the beneficial roles of adipokines on body metabolism and its profound protective effects against metabolic disease, a better understanding of the regulation of adipokines secretion is very important. The objective of this study was to isolate, detect and quantify the total proteins in trimmed off abdominal adipose tissues from halal meat sources namely chicken, beef and lamb. Abdominal adipose tissues were isolated from the aforementioned sources and delipidation of the tissues were performed by chloroform/methanol extractions. Then, the protein concentration was determined by using Protein Assay Bicinchoninate Kit method. This was followed by quantification of the adipokines using ELISA kit assay. The experiment was conducted in triplicates and the results are presented as means ± SD. Results indicate that the extraction of 10 gram subcutaneous adipose tissues from chicken, beef and lamb yielded 0.10 gram ofprotein amount which was 1.0 % from total tissue mass. The protein concentration in adipose tissue of chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml respectively. The isolated adiponectin concentration in chicken, beef and lamb were 158 ng/ml± 0.05, 24 ± 0.05µg/ml and 37 ± 0.08 ng/ml respectively. These sources will bear further investigation on isolation and formulation for diabetic rat models in near future. Keywords: Adipose tissue, protein, adiponectin